A clinical efficacy experience of Lacosamide on sleep quality in patients with Nocturnal Frontal Lobe Epilepsy (NFLE) - Mangiardi, Marilena; Alfano, Guido (Acta Biomedica Atenei Parmensis, 2018)
Background: Nocturnal frontal lobe epilepsy (NFLE) is a focal epilepsy with seizures arising mainly during sleep and characterized by complex motor behavior or sustained dystonic posturing. First described in 1981, it was considered a motor disorder of sleep and was indicated as nocturnal paroxysmal dystonia (NPD). The debated on epileptic origin of this condition was demonstrated in 1990 and the term NFLE was introduced. Since then it has been demonstrated that the heterogeneous aspects of morpheic seizures were responsive to antiepileptic drugs (AED’s) with sodium blocking action mechanism, especially the carbamazepine (CBZ). Aim of Work and Methods: We report a clinical experience of NFLE patients associated with sleep disorders treated with Lacosamide, AED’s with a novel mechanism of action. In vitro electrophysiology studies have shown that lacosamide selectively boosts the slow inactivation of the sodium-voltage-dependent channels, resulting in a stabilization of the hypersensitive neuronal membranes. Results and Conclusion: On the treated patients we observed a positive clinical response to lacosamide therapy without significant side effects. In particular, the effective clinical response to the pharmacological treatment was obtained at a dose of 200 mg/day.